Answer:
6
Step-by-step explanation:
6
Answer:
B maybe? that doesnt equal any
Step-by-step explanation:
f(x)=3x^2+6x
f(2)=3(2)^2+6(2)
f(2)=3(4)+12
f(2)=12+12
f(2)=24
I used a dash line because the term 'less than' does not include the value itself.
The vertex of the equation is ( -2 , -2 )
The axis of symmetry is x= - 2
n ∈ natural even numbers
Step-by-step explanation:
1 + 3 + 5 + 7 + … + (2n-1)
sum of the first n terms :
Sₙ = n/2(a + Uₙ)
Sₙ = n/2(1 + 2n - 1)
Sₙ = n/2(2n)
Sₙ = n²
∴ so, the solution of n is all natural even numbers